Sanksi Hukum Terhadap Perseroan Terbatas yang Tidak Berbadan Hukum - Nurdini Dwi Septi; Alfina Damayanti; Sumriyah Sumriyah (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
A limited liability company (PT) is a legal entity that is generally used to run business in various countries. The process of establishing a PT involves steps such as determining the company name, preparing articles of association, and registration with a n authorized legal entity. After establishment, shareholders play a role in determining Company policy through general shareholder meetings (GMS) and electing the board of directors. The purpose of this research is to find out the conditions for establishing a PT in Indonesia and what legal sanctions there are for PTs that do not have legal principles.